Qurmatica-Based Learning as a Solution to Reduce Anxiety for Students' Mathematics Phobias - Yoga Klody Arianto; Veronika Dwi Cahyani; Lutviatul Hasana; Abdul Halim Fathani (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
Mathematics anxiety is an obstacle for students in carrying out mathematics learning, especially there are still students who think mathematics is a difficult and boring subject. The ability to understand mathematical concepts of each student is different. There are several influencing factors, one of which is the anxiety experienced by students when learning mathematics. Therefore, mathematics is one of the important lessons to be learned, not only students at school but also students who are studying in Islamic boarding schools. Some of the knowledge that students learn in Islamic boarding schools also requires mathematics. For example, when studying the science of zakat distribution, Faraid science, and the like. The students have applied the linkage of mathematical concepts with Islamic concepts studied by students in Islamic boarding schools. In this study, the data collection method used was a literature study. This method was used to obtain additional literature data from reference books regarding mathematics anxiety towards students. In fact, mathematics is a basic science that is important for the advancement of science and technology, and the concepts in learning mathematics are used in everyday life. The author tries to offer a solution to reduce the level of anxiety of students towards mathematics by conducting learning that integrates the Qur'an with mathematics using the QURMATICA method as a solution can be used to play and learn mathematics and to encourage students' enthusiasm in learning mathematics and students can reduce their mathematics anxiety.